Not in our remit (Refugee Studies Centre, University of Oxford, 2014)
When secular organisations are responding to the needs of displaced people, the religious practices and needs of the communities may not be high on the list of things to be thought about. Indeed secular organisations may struggle to recognise the importance of religion, in life and in death.